Endophyte genomes support greater metabolic gene cluster diversity compared with non-endophytes in Trichoderma - Scott, Kelsey; Konkel, Zachary; Gluck-Thaler, Emile; Valero David, Guillermo E.; Simmt, Coralie Farinas; Grootmyers, Django; Chaverri, Priscila; Slot, Jason (PLOS ONE, 2023)
Trichoderma is a cosmopolitan genus with diverse lifestyles and nutritional modes, including mycotrophy, saprophytism, and endophytism. Previous research has reported greater metabolic gene repertoires in endophytic fungal species compared to closely-related non-endophytes. However, the extent of this ecological trend and its underlying mechanisms are unclear. Some endophytic fungi may also be mycotrophs and have one or more mycoparasitism mechanisms. Mycotrophic endophytes are prominent in certain genera like Trichoderma, therefore, the mechanisms that enable these fungi to colonize both living plants and fungi may be the result of expanded metabolic gene repertoires. Our objective was to determine what, if any, genomic features are overrepresented in endophytic fungi genomes in order to undercover the genomic underpinning of the fungal endophytic lifestyle. Here we compared metabolic gene cluster and mycoparasitism gene diversity across a dataset of thirty-eight Trichoderma genomes representing the full breadth of environmental Trichoderma’s diverse lifestyles and nutritional modes. We generated four new Trichoderma endophyticum genomes to improve the sampling of endophytic isolates from this genus. As predicted, endophytic Trichoderma genomes contained, on average, more total biosynthetic and degradative gene clusters than non-endophytic isolates, suggesting that the ability to create/modify a diversity of metabolites potential is beneficial or necessary to the endophytic fungi. Still, once the phylogenetic signal was taken in consideration, no particular class of metabolic gene cluster was independently associated with the Trichoderma endophytic lifestyle. Several mycoparasitism genes, but no chitinase genes, were associated with endophytic Trichoderma genomes. Most genomic differences between Trichoderma lifestyles and nutritional modes are difficult to disentangle from phylogenetic divergences among species, suggesting that Trichoderma genomes maybe particularly well-equipped for lifestyle plasticity. We also consider the role of endophytism in diversifying secondary metabolism after identifying the horizontal transfer of the ergot alkaloid gene cluster to Trichoderma.